Profil Kepribadian Big Five dan Collecting Behaviour Kolektor Piringan Hitam - nugrahawati, eni nuraeni; Arista, Destianty (Psympathic : Jurnal Ilmiah Psikologi, 2016)
A collector has peculiarities in their behavior, they have an emotional bond with his collection, persistent in hunting collection and preserved in caring, worried about the loss and damage of his/her collections. This study focused on how the collector’s personality profile and behavior on collecting records by using the theory of the Big Five Personality Profile from McIntosh & Schmeichel. The subjects of research were collector of records aged 30 to 39 years old with the level of social status was medium. By factors analysis through International Item Pool Representation (IPIP-NEO) questionnaire from Goldberg, this research found that type personality mostly were the openess to experience was high, Counscientiousness was high, Extraversion was high, Agreeableness was high, and Neuroticsm was low (O↑C↑E↑A↑N↓). Additionally the Collecting Behaviour type were the Passionate was high, the Inquisitive was low, the Hobby was high and the Expressive was high (P↑I↓H↑E↑).